Interaction on facebook and twitter: The ten main radio [Interacción en facebook y twitter: Las diez principales emisoras de radio ecuatorianas] - Martinez Ruque, H. (2015)
The research was conducted by analyzing Facebook and Twitter. The methodology begins with a census that identifies the ten stations with the most interaction in social networks, than conducted an ethnographic analysis; finally, we contrasted the results through an interview. With the intention to understand the dialogue between the media and their audiences. Demonstrating public policies regarding communication. © 2016, Universidad del Zulia. All rights reserved.